Context-free languages of sub-exponential growth - Bridson, M; Gilman, R (Elsevier, 2002)
Context-free languages of sub-exponential growth were studied. The growth function was defined as the function whose value at each non-negative integer was the number of words of length n in a fixed formal language. The definition of a bounded language, which is a subset for some words, was also used in the analysis. Results showed that context-free languages of intermediate growth were nonexistent.